Adhesive layer and bonding method for composite material component of equal diameter or small taper rotation body and metal structure

By embedding fiber felts in the adhesive layer between the composite material and the metal structure, and combining the guide gap design, the problem of glue gap lacking during the bonding process of the rotary composite material and the metal structure is solved, and high strength and good heat dissipation performance are achieved.

CN117965128BActive Publication Date: 2025-03-14长沙思云新材料科技有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410131201.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-31
Publication Date
2025-03-14
Estimated Expiration
2044-01-31

AI Technical Summary

Technical Problem

The prior art has problems with glue gaps during the bonding process between the rotary composite material and the metal structure, resulting in insufficient bonding strength and degradation of heat dissipation performance.

Method used

The structure of embedded fiber felt between the two inner and outer bonding layers is adopted to enhance the strength and filling ability of the bonding adhesive layer through the elasticity and porosity of the fiber felt, and the problem of uneven assembly gap is solved by using the guided gap design.

Benefits of technology

High-strength bonding between composite materials and metal structures is achieved, and the role of a thermal strain isolation pad is played, avoiding the occurrence of glue-loss gaps and improving the thermal heat dissipation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117965128B_ABST
    Figure CN117965128B_ABST
Patent Text Reader

Abstract

The present invention discloses an adhesive layer and a bonding method for an equal-diameter or small-tapered rotating composite material component and a metal structure. The adhesive layer is designed as a composite structure of an inner adhesive layer + a fiber felt with internal adhesive penetration + an outer adhesive layer, which is used for bonding between the composite material component and the metal structure, giving the composite material component and the metal structure a higher bonding strength, and can act as a thermal strain isolation pad. In particular, the designed adhesive layer is used in the bonding process of an equal-diameter or small-tapered rotating composite material component and a metal structure, which can solve the technical problem of debonding due to friction when the equal-diameter or small-tapered rotating composite material component is sleeved on the metal structure. At the same time, a guided fixed gap design is used to solve the technical problem of uneven assembly gaps caused by deformation of two equal-diameter or small-tapered rotating components, and can be widely used in the field of thermal protection assembly of aerospace vehicles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an adhesive layer, in particular to an adhesive layer for bonding composite materials to metal materials, and also to a method for bonding a composite material component of an equal-diameter or small-taper body of revolution to a metal structure, belonging to the technical field of thermal protection material assembly for aerospace. Background Art

[0002] Thermal protection and thermal management of the outer surface of aerospace vehicles have always been a key part of aircraft design and application. With the development of domestic aerospace vehicles, various thermal protection materials have also developed rapidly. At present, thermal protection materials are mainly fiber-reinforced resin-based or ceramic-based composite materials. Thermal protection materials mainly provide heat protection and heat insulation for the outer surface by bonding to the metal load-bearing structure.

[0003] In practical applications, the bonding of thermal protection materials includes spraying and bonding the composite materials in blocks according to the designed dimensions to the metal structure; or the composite materials of the rotating body structure are put on the metal cylindrical cabin section, and the adhesive is used in the middle. The main consideration for the block-bonded structural parts is the bonding strength, which can basically ensure the fullness of the glue layer; and when the rotating body-shaped composite material set is bonded to the metal cabin, due to the unavoidable slight thermal deformation during the forming process of the cylindrical composite material component, and the relative displacement process between the material and the metal structure surface during assembly, the wet glue layer sprayed on the surface of the metal structure in advance during the assembly bonding process is basically difficult to retain, resulting in a large number of glue-deficient gaps in the assembly gap after the bonding process is completed. On the one hand, the glue-deficient state makes the position basically have no bonding strength, and on the other hand, a large number of glue-deficient gaps may significantly reduce the heat sink at this position, bringing the risk of local ineffective heat dissipation.

[0004] When the components of the large-taper cabin section are assembled, the bonding surfaces of the two rotating structures are usually basically in contact when they are about to be assembled in place (such as Figure 1 As shown in the figure, the distance between the two structural assembly surfaces is relatively large at the beginning of the assembly process from top to bottom), and the two rotating structures can find the centering angle by themselves and rely on the thickness of the adhesive layer to control the assembly accuracy. However, when designing cabin sections, there are usually some rotating cabin sections with equal diameters (usually a small taper of 0 to 2° has a greater impact on the overall structure), and when the rotating composite materials of equal diameters are assembled with the metal cabin, the bonding gap is usually designed to be small (the deformation of the material may be greater than the bonding gap size), so that the effect of high-precision assembly cannot be achieved, and the composite components and the metal cabin are quickly in contact with the adhesive layer after the axial assembly begins (such as Figure 1 As shown in the figure, due to the friction, the glue layer on the surface of the metal structure is basically scraped away by the inner surface of the composite material component with relative displacement. Summary of the invention

[0005] In view of the shortcomings of the existing bonding technology, the first object of the present invention is to provide an adhesive layer, which is used for bonding composite materials and metal materials and not only has a high overall bonding strength but also can act as a thermal strain isolation pad.

[0006] The second object of the present invention is to provide a method for bonding equal-diameter or small-tapered rotating composite material components to metal structures. The method adopts a special bonding layer structure to give the equal-diameter or small-tapered rotating composite material components and the metal structure a higher overall bonding strength, and can act as a thermal strain isolation pad. The fiber felt bonding method is used to solve the technical problem of debonding due to friction when the equal-diameter or small-tapered rotating composite material components are sleeved on the metal structure. At the same time, a guided fixed gap design is used to solve the technical problem of uneven assembly gaps caused by deformation of two equal-diameter or small-tapered rotating components. The method can solve the technical difficulties existing in the assembly process of equal-diameter rotating composite material components and metal structures, and can also be promoted and used in the assembly process of other small-tapered rotating composite material structures. It has broad application prospects in the field of thermal protection assembly of aerospace vehicles.

[0007] In order to achieve the above technical purpose, the present invention provides an adhesive layer for bonding composite materials to metal materials, which comprises, from inside to outside, an inner adhesive layer, an internally infiltrated fiber felt and an outer adhesive layer.

[0008] The adhesive layer of the present invention is mainly used to bond the composite material component of the rotating body to the metal structure of the bearing structure. The adhesive layer is a structure of inner adhesive layer + fiber felt (internal adhesive penetration) + outer adhesive layer (specifically, Figure 2 As shown). By using fiber felt in the middle of the adhesive layer, the fiber felt has good elasticity and porous structure, which plays a good reinforcing role on the entire adhesive layer. The fiber felt infiltrated with adhesive can ensure that the entire adhesive layer can fully fill the bonding gap after the assembly of the rotating composite material component and the metal structure is completed, avoiding the problem of a large amount of adhesive shortage. At the same time, the entire adhesive layer can play the role of a thermal strain isolation pad.

[0009] As a preferred solution, the inner adhesive layer and the outer adhesive layer are both selected from at least one of silicone rubber, polyurethane adhesive, polyimide adhesive, and epoxy resin adhesive, which are common adhesive types for bonding composite components and metal structures in the prior art.

[0010] As a preferred solution, the fiber felt is selected from at least one of quartz fiber needle felt, glass fiber needle felt, and polyimide fiber felt.

[0011] The present invention also provides a method for bonding a composite material component of a rotating body of equal diameter or small taper to a metal structure, the method comprising the following steps:

[0012] 1) Fix the metal cylindrical component upright on the platform along the axis, and evenly arrange the positioning stainless steel wires on its outer surface;

[0013] 2) Apply adhesive I evenly on the outer surface of the metal cylindrical component;

[0014] 3) Laminating the fiber felt on the surface of the adhesive I, and then evenly brushing the adhesive II on the surface of the fiber felt, the adhesive II completely penetrates the fiber felt, and a layer of adhesive II is evenly brushed on the surface of the fiber felt; the viscosity of the adhesive I is higher than that of the adhesive II;

[0015] 4) Apply a layer of adhesive II evenly on the inner surface of the composite cylindrical component;

[0016] 5) Sleeve the composite cylindrical component onto the surface of the metal cylindrical component;

[0017] 6) The assembled overall component is subjected to heat curing treatment, and then the positioning stainless steel wire is removed.

[0018] The present invention is mainly a solution to the technical problems existing in the bonding process of composite material components of equal-diameter or small-taper bodies of revolution and metal structures. For conical bodies of revolution, there are no technical problems such as easy debonding during the assembly process and easy deformation of composite material components of the revolution, resulting in uneven assembly. Moreover, the smaller the taper of the composite material component of the revolution, the more obvious these phenomena are during the bonding process with the metal structure. In the bonding process of the metal cylindrical component and the composite cylindrical component of equal diameter or small taper rotation body, the present invention first brushes the high viscosity adhesive glue I on the surface of the metal cylindrical component, so that the fiber felt can be well attached to the outer surface of the metal cylindrical component, and the fiber felt attached to the outer surface of the metal cylindrical component has a good reinforcing and protective effect on the adhesive layer formed by the high viscosity adhesive glue I. When the composite cylindrical component is assembled, the adhesive layer formed by the adhesive glue I is not easy to be interrupted and scraped away, and the fiber felt has good elasticity. The fiber felt body adsorbed with the adhesive glue can ensure that the entire adhesive layer fully fills the bonding gap when the assembly is completed, and the low viscosity adhesive glue II brushed on the outer layer can penetrate into the fiber felt to make it fully wetted. At the same time, the adhesive layer formed by the low viscosity adhesive glue II plays a good lubricating role, which is conducive to the sliding process of the composite component from top to bottom. At the same time, the present invention evenly arranges the positioning stainless steel wire on the surface of the metal cylindrical component, and solves the problem of uneven assembly gap caused by the deformation of the composite material of the two equal diameter or small taper rotation body structural parts by adopting the design of fine stainless steel wire guiding the fixed gap.

[0019] As a preferred solution, the composite cylindrical member is composed of at least one of a fiber-reinforced resin-based composite material and a fiber-reinforced ceramic-based composite material, with a thickness of 5 to 30 mm, an inner diameter of 300 to 2000 mm, and a height of 300 to 2000 mm. As a preferred solution, the metal cylindrical member is composed of at least one of an aluminum alloy, stainless steel, and a titanium alloy, with a wall thickness of 2 to 20 mm, a height consistent with that of the composite cylindrical member, and an outer diameter of 0.3 to 1 mm smaller than the inner diameter of the composite cylindrical member (i.e., a bonding gap of 0.3 to 1 mm). The inner wall of the composite cylindrical member and the outer wall of the metal cylindrical member (i.e., the bonding surface) are cylindrical.

[0020] As a preferred solution, the positioning stainless steel wires are evenly arranged along the height direction of the outer surface of the metal cylindrical component, and the arc length between any two positioning stainless steel wires is 50 to 150 mm; the diameter of the positioning stainless steel wire is consistent with the thickness of the bonding layer. The present invention uses positioning stainless steel wires to achieve guided fixed gaps, which can solve the problem of uneven assembly gaps caused by deformation of the two rotating components. The main function of the positioning stainless steel wires is to guide and position the bonding gap between the metal cylindrical component and the composite material cylindrical component through a number of stainless steel wires that are parallel to the outer surface of the cylinder (in the height direction) (such as Figure 2 shown).

[0021] As a preferred solution, the viscosity of the adhesive I is 2000-10000 mPa·s. The viscosity of the adhesive I is relatively large, which allows the fiber felt to be well attached to the outer surface of the metal cylindrical component. The fiber felt is attached to the surface of the adhesive I, and has a good reinforcing effect on the adhesive layer, so that the adhesive layer is not easily interrupted and scraped away during the assembly process of the composite cylindrical component and the metal cylindrical component. At the same time, the fiber felt has good elasticity and porous structure, and the fiber felt adsorbed with the adhesive can ensure that the entire adhesive layer fully fills the bonding gap when the assembly is completed. If the viscosity of the adhesive I is too large, it is not conducive to uniform brushing. If the viscosity is too small, it is easy to flow and is not conducive to wall hanging. The viscosity of the adhesive I is further preferably 2000-5000 mPa·s.

[0022] As a preferred solution, the viscosity of the adhesive II is 100-1000 mPa·s. The adhesive II applied on the outer layer has a relatively low viscosity. On the one hand, the adhesive can penetrate well into the entire fiber felt to fully wet it. On the other hand, the low viscosity adhesive layer on the surface can play a good lubricating role, which is beneficial to the relative sliding process between the components during the assembly of the composite cylindrical component and the metal cylindrical component. Viscosity adjustment is achieved by adding a diluent. Too high a viscosity is not conducive to infiltration into the felt body. Too low a viscosity will result in low bonding strength if too much diluent is added. The viscosity of the adhesive II is further preferably 500-800 mPa·s.

[0023] As a preferred solution, the adhesive glue I and the adhesive glue II are both selected from silicone rubber, polyurethane glue, polyimide glue or epoxy resin glue. The adhesive glue I and the adhesive glue II are further preferably silicone rubber or polyurethane glue, which are high temperature resistant, low curing temperature and good toughness after bonding. These adhesive glues are all conventional commercial reagents in the prior art.

[0024] As a preferred solution, the fiber felt is selected from at least one of quartz fiber needle felt, glass fiber needle felt, and polyimide fiber felt. The fiber felt is further preferably at least one of quartz fiber needle felt or glass fiber felt. Quartz fiber needle felt and glass fiber needle felt have good temperature resistance and good wettability with the adhesive, which is conducive to the full penetration of the adhesive II.

[0025] As a preferred solution, the inner surface of one end of the composite cylindrical member is processed into an oblique opening (such as Figure 3 As shown), the inner diameter of the port is increased by 2 to 4 mm. As a more preferred solution, the bevel section is further preferably 10 to 20 mm, which can not only play a role in expanding the port bonding gap, but also minimize the impact on the heat protection and insulation performance of the composite material component port.

[0026] As a preferred solution, the conditions of the thermal curing treatment are: temperature of 40 to 100° C. and time of 30 to 60 hours.

[0027] The present invention provides a method for bonding a composite material component of a rotating body of equal diameter or small taper to a metal structure, which specifically comprises the following steps:

[0028] 1) Fix the metal cylindrical component to the platform in an upright direction, with the end with the larger outer diameter facing downward (if it is a rotating body with equal diameter, the upper and lower ends are determined according to specific needs, mainly considering the assembly relationship with the composite material structure) and evenly arrange positioning stainless steel wires on its outer surface, and the positioning stainless steel wires are parallel to the outer surface of the cylinder (straightened in the height direction);

[0029] 2) Evenly apply high-viscosity adhesive I on the outer surface of the metal cylindrical component;

[0030] 3) A layer of fiber felt is attached to the surface of the high-viscosity adhesive I, so that the length of the fiber felt is 200-300 mm higher than the height of the metal cylindrical component, the lower end of the fiber felt is flush with the lower end of the metal cylindrical component, and the extra section at the upper end is turned over to the inside of the metal cylindrical component for fixing; the fiber felt is cut open at the position where the steel wire is present to avoid overlapping thickness of the fiber felt and the steel wire;

[0031] 4) Apply low-viscosity adhesive II evenly on the fiber felt surface of the outer surface of the metal cylindrical component, so that the adhesive II completely penetrates the fiber felt, and a layer of adhesive II is applied on the fiber felt surface. At the same time, apply low-viscosity adhesive II on the inner surface of the composite cylindrical component until it is fully applied;

[0032] 5) Fit the composite cylindrical component onto the outer surface of the metal cylindrical component from top to bottom, and apply a certain pressure on the upper end surface of the material during the fitting process to fit it into place;

[0033] 6) Place the assembled and bonded components in an oven to keep them warm according to the process requirements of the adhesive, remove the stainless steel wire, and clean up excess fiber felt and colloid.

[0034] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:

[0035] 1) The adhesive layer provided by the present invention for bonding composite material components and metal structures adopts the method of adhesive layer + fiber felt + adhesive layer. On the one hand, the adhesive layer has good bonding strength as a whole; on the other hand, the adhesive layer plays the role of a thermal strain isolation pad.

[0036] 2) The bonding method of equal-diameter or small-tapered rotating composite material components and metal structures provided by the present invention solves the problem of uneven assembly gaps between the two rotating structural parts caused by deformation of the composite materials by adopting a design of a thin stainless steel wire guide to set the gap (the stainless steel wire can be removed after the bonding is completed).

[0037] 3) The bonding method of equal-diameter or small-tapered rotational composite material components and metal structures provided by the present invention solves the technical difficulty that the glue layer slides away in large quantities due to the friction generated by the relative movement between the two components when the equal-diameter rotational composite material components are sleeved on the metal structure, by applying glue twice and arranging a layer of fiber felt in the middle of the glue layer. At the same time, it avoids the problem of a large amount of glue shortage in the adhesive layer after bonding.

[0038] 4) The bonding method for equal-diameter or small-taper rotational composite material components and metal structures provided by the present invention is aimed at the difficulty of assembling equal-diameter or small-taper rotational composite material components with metal structures under the conditions of local deformation and small bonding gap. The inner surface of one end of the composite cylindrical component is processed into an oblique mouth 5 to 50 mm inward from the port, and the taper of the component port is increased in a small range. This does not affect the overall strength and heat-insulating performance of the composite component, and prevents the two cylindrical components from contacting the glue layer when they are just put together. The guiding and positioning functions of the metal wire can be smoothly realized, further optimizing the sleeve assembly scheme.

[0039] In summary, the present invention can solve the technical difficulties in assembling composite material components of equal-diameter or small-tapered bodies of revolution and metal structures, and can also be promoted and used in the assembly process of composite materials of other small-tapered bodies of revolution structures, and has broad application prospects in the field of thermal protection assembly of aerospace vehicles. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 It is a schematic diagram of the bonding process of large-tapered rotating body components and equal-diameter rotating body sets.

[0041] Figure 2 This is a schematic diagram of the assembly and bonding of equal-diameter rotating body components (top view).

[0042] Figure 3 This is a schematic diagram (cross-section) of the assembly and bonding of equal-diameter rotating components.

[0043] Figure 4 This is a photo of Example 1 disassembled into pieces after bonding.

[0044] Figure 5 This is a physical picture of the adhesive layer on the surface of the material after being disassembled after bonding in Comparative Example 1.

[0045] Among them, 1 is a metal cylindrical component, 2 is a positioning stainless steel wire, 3 is an adhesive layer I, 4 is a fiber felt, 5 is an adhesive layer II, 6 is a composite cylindrical component, 7 is an equal-diameter rotating composite component with the bottom inner surface processed as a bevel position, 8 is a composite material that is firmly bonded during the disassembly process and is torn, 9 and 10 are unbonded states (the smooth surface that appears after disassembly indicates direct stratification at this location and incomplete glue), 9 is a rough scratch formed by the adhesive being scraped away, 10 is a bright surface formed by a large area of ​​hollow state due to incomplete glue in the bonding gap, and 11 is the state after disassembly of a small area of ​​full glue layer (the glue layer is torn during the disassembly process). DETAILED DESCRIPTION

[0046] The following specific examples are intended to further illustrate the present invention in detail, rather than to limit the scope of protection of the claims.

[0047] Example 1

[0048] A quartz fiber reinforced phenolic resin aerogel composite material with an inner diameter of 760 mm, an outer diameter of 800 mm, and a height of 700 mm is used as an equal diameter component (the bottom end surface is processed into an oblique opening at a depth of 20 mm inward, such as Figure 3 As shown, the inner diameter of the bottom end face is enlarged to 762mm, the thickness at the end face is changed to 19mm, the bonding gap is enlarged from 0.5mm to 1.5mm, and there is no obvious effect on the heat insulation performance of the raw materials). The bonding method of the present invention is described by taking the bonding with an aluminum alloy cylindrical component with a wall thickness of 5mm, an outer diameter of 759mm, and a height of 700mm as an example. Specifically, the following steps are included:

[0049] 1) An aluminum alloy cylindrical component with a wall thickness of 5 mm, an outer diameter of 759 mm, and a height of 700 mm is fixed to the platform in an upright direction, and 24 φ0.5 mm positioning stainless steel wires are evenly arranged on its outer surface, parallel to the outer surface of the aluminum alloy cylindrical component, and the arc length of the steel wires is arranged at about 100 mm (straightened in the height direction, and wound around the inside of the cylindrical component to be butt-jointed and tightened);

[0050] 2) Apply silicone rubber adhesive (glue layer I, viscosity is about 2500mPa·s, curing process requires 60°C insulation for 48 hours) evenly on the outer surface of the metal cylindrical component;

[0051] 3) Paste a layer of glass fiber mat (fiber mat surface density is about 200g / m 2 ), so that the length of the felt body is about 200mm higher than the height of the metal cylindrical component, the lower end of the fiber felt is flush with the bottom end of the aluminum alloy cylindrical component, and the extra section of the upper end is turned over to the inside of the aluminum alloy cylindrical component for fixing; the fiber felt is cut open at the position where the steel wire is to allow the steel wire to leak out to avoid overlapping thickness of the fiber felt and the steel wire;

[0052] 4) Apply silicone rubber adhesive (glue layer II, viscosity is about 600mPa·s, curing process requires 48 hours of heat preservation at 60℃) evenly on the fiber felt surface of the metal cylindrical component, so that the adhesive completely penetrates the fiber felt and the surface is covered with a layer of adhesive. At the same time, apply adhesive on the inner surface of the composite material component. The adhesive used is consistent with that of glue layer II, and it can be covered completely.

[0053] 5) Fit the phenolic resin aerogel composite material component onto the outer surface of the aluminum alloy cylindrical component from top to bottom, and apply a certain pressure to the upper end surface of the material during the fitting process (specifically, tooling and pressure devices can be used) to fit it into place;

[0054] 6) Place the assembled and bonded components in an oven at 60°C for 48 hours, remove the stainless steel wire, and clean up excess fiber felt and colloid.

[0055] Example 2

[0056] Taking the bonding of a fiber-reinforced ceramic composite material component with an inner diameter of 350 mm, an outer diameter of 380 mm, and a height of 800 mm as an example, the bonding method of the present invention is described by bonding a fiber-reinforced ceramic composite material component with an inner diameter of 350 mm, an outer diameter of 380 mm, and a height of 800 mm (the bottom end surface is processed into a bevel at a depth of 30 mm inward, so that the inner diameter of the bottom end surface is expanded to 352 mm, the thickness at the end surface is changed to 14 mm, the bonding gap is expanded from 0.8 mm to 1.8 mm, and there is no obvious effect on the heat insulation performance of the raw materials) with an aluminum alloy cylindrical component with a wall thickness of 4 mm, an outer diameter of 348.4 mm, and a height of 800 mm. Specifically, the following steps are included:

[0057] 1) An aluminum alloy cylindrical component with a wall thickness of 4 mm, an outer diameter of 348.4 mm, and a height of 800 mm is fixed to the platform in an upright direction, and 18 φ0.8 mm positioning stainless steel wires are evenly arranged on its outer surface, parallel to the outer surface of the aluminum alloy cylindrical component, and the arc length of the steel wires is about 60 mm (straightened in the height direction, and wound around the inside of the cylindrical component to be butt-jointed and tightened);

[0058] 2) Apply epoxy resin adhesive (glue layer I, viscosity is about 4000mPa·s, curing process requires 40°C insulation for 60 hours) evenly on the outer surface of the metal cylindrical component;

[0059] 3) Paste a layer of quartz fiber felt on the surface of adhesive layer I (fiber felt surface density is about 300g / m 2 ), so that the length of the felt body is about 300mm higher than the height of the metal cylindrical component, the lower end of the fiber felt is flush with the bottom end of the aluminum alloy cylindrical component, and the extra section of the upper end is turned over to the inside of the aluminum alloy cylindrical component for fixing; the fiber felt is cut open at the position where the steel wire is to allow the steel wire to leak out to avoid overlapping thickness of the fiber felt and the steel wire;

[0060] 4) Apply epoxy resin adhesive (glue layer II, viscosity is about 1000mPa·s, curing process requires 60 hours of heat preservation at 40℃) evenly on the fiber felt surface of the metal cylindrical component, so that the glue completely penetrates the fiber felt and the surface is covered with a layer of glue. At the same time, apply glue on the inner surface of the composite material component. The adhesive used is consistent with glue layer II, and it can be fully coated.

[0061] 5) Fit the fiber-reinforced ceramic composite material component onto the outer surface of the aluminum alloy cylindrical component from top to bottom, and apply a certain pressure to the upper end surface of the material during the fitting process (specifically, tooling and pressure devices can be used) to fit it into place;

[0062] 6) Place the assembled and bonded components in an oven at 40°C for 60 hours, remove the stainless steel wire, and clean up excess fiber felt and colloid.

[0063] Comparative Example 1

[0064] Similarly, a quartz fiber reinforced phenolic resin aerogel composite material with an inner diameter of 760 mm, an outer diameter of 800 mm, and a height of 700 mm was bonded to an aluminum alloy cylindrical component with a wall thickness of 5 mm, an outer diameter of 759 mm, and a height of 700 mm (the bottom end surface was also processed into an oblique opening at a depth of 20 mm inward, such as Figure 3 As shown, the inner diameter of the bottom end face is enlarged to 762mm, the thickness at the end face is changed to 19mm, the bonding gap is enlarged from 0.5mm to 1.5mm, and there is no obvious effect on the heat insulation performance of the raw materials). The method of directly brushing the bonding glue set is as follows:

[0065] 1) Fix the aluminum alloy cylindrical component with a wall thickness of 5mm, an outer diameter of 759mm, and a height of 700mm to the platform in an upright direction (directly apply glue without installing steel wire);

[0066] 2) Apply silicone rubber adhesive (viscosity is about 2500mPa·s, and the curing process requires 48 hours of heat preservation at 60℃) evenly on the outer surface of the metal cylindrical component and the inner surface of the composite material component. The total thickness of the adhesive is greater than 0.5mm to ensure that there is enough adhesive.

[0067] 3) Fitting the phenolic resin aerogel composite material component onto the outer surface of the aluminum alloy cylindrical component from top to bottom, applying a certain pressure on the upper end surface of the material during the fitting process (specifically, tooling and pressure devices can be used) to fit it into place;

[0068] 4) Place the assembled and bonded components in an oven at 60°C for 48 hours, and then clean off excess fiber felt and colloid.

[0069] After disassembly, it was found that the bonding rate of Example 1 and Example 2 was more than 95%. When the composite material was disassembled into small pieces, it was found that the material was firmly bonded. In most places, the adhesive layer was still adhered to the outer surface of the metal structure when the material was torn apart (such as Figure 4 As shown). Comparative Example 1 was dissected and found to have a debonding rate of more than 80%. When the composite material was disassembled into small pieces, it was found that the material was basically not bonded to the metal structure and the material could be easily peeled off. On the one hand, the adhesive part of the inner surface of the material showed a bright surface, indicating that the adhesive on the outer surface of the metal structure and the adhesive on the inner surface of the composite material did not combine during the assembly process, resulting in a hollow bonding gap. After drying, it was completely unbonded and showed a bright surface; on the other hand, a large number of rough scratches appeared on the surface (such as Figure 5 As shown in the figure, it means that there is a local unevenness on the bonding surface of the composite cylindrical component and the metal structure. When the composite cylindrical component and the metal structure are assembled, the glue layer is carried away by the local high point due to the relative movement, and there is no subsequent colloid replenishment, resulting in a large area of ​​glue deficiency.

Claims

1. A method for bonding a composite material component of a rotating body of equal diameter or small taper to a metal structure, characterized in that: The following steps are involved: 1) Fix the metal cylindrical component upright on the platform along the axis, and evenly arrange the positioning stainless steel wire on its outer surface; 2) Apply adhesive I evenly on the outer surface of the metal cylindrical component; 3) Laminating the fiber felt on the surface of the adhesive I, and then evenly brushing the adhesive II on the surface of the fiber felt, the adhesive II completely penetrates the fiber felt, and a layer of adhesive II is evenly brushed on the surface of the fiber felt; the viscosity of the adhesive I is higher than that of the adhesive II; 4) Apply a layer of adhesive II evenly on the inner surface of the composite cylindrical component; 5) Sleeve the composite cylindrical component onto the surface of the metal cylindrical component; 6) Heat cure the assembled components and then remove the positioning stainless steel wire.

2. The bonding method of a composite material component of a rotating body of equal diameter or small taper to a metal structure according to claim 1, characterized in that: The composite cylindrical member is composed of at least one of a fiber-reinforced resin-based composite material and a fiber-reinforced ceramic-based composite material, and has a thickness of 5 to 30 mm, an inner diameter of 300 to 2000 mm, and a height of 300 to 2000 mm; The metal cylindrical component is made of at least one of aluminum alloy, stainless steel, and titanium alloy, has a wall thickness of 2 to 20 mm, a height consistent with that of the composite cylindrical component, and an outer diameter 0.3 to 1 mm smaller than the inner diameter of the composite cylindrical component.

3. The bonding method of a composite material component of a rotating body of equal diameter or small taper to a metal structure according to claim 1, characterized in that: The positioning stainless steel wires are evenly arranged along the height direction of the outer surface of the metal cylindrical component, and the arc length of the interval between any two positioning stainless steel wires is 50-150 mm; the diameter of the positioning stainless steel wire is consistent with the thickness of the bonding layer.

4. The bonding method of a composite material component of a rotating body of equal diameter or small taper to a metal structure according to claim 1, characterized in that: The viscosity of the adhesive I is 2000-10000 mPa•s; The viscosity of the adhesive II is 100-1000 mPa•s; The adhesive glue I and the adhesive glue II are both selected from silicone rubber, polyurethane glue, polyimide glue or epoxy resin glue.

5. The bonding method of a composite material component of a rotating body of equal diameter or small taper to a metal structure according to claim 1, characterized in that: The fiber felt is selected from at least one of quartz fiber needle felt, glass fiber needle felt and polyimide fiber felt.

6. The bonding method of a composite material component of a rotating body of equal diameter or small taper to a metal structure according to claim 1, characterized in that: The inner surface of one end of the composite material cylindrical component is processed into an oblique opening within a range of 5 to 50 mm inward from the port, so that the inner diameter at the port is increased by 2 to 4 mm.

7. The bonding method of a composite material component of a rotating body of equal diameter or small taper to a metal structure according to claim 1, characterized in that: The conditions of the thermal curing treatment are: a temperature of 40 to 100° C. and a time of 30 to 60 hours.

Citation Information

Patent Citations

  • Double-sided all-purpose adhesive tape

    CN102965047A

  • A polyimide carrier adhesive film and a preparing method thereof

    CN108611002A

  • Toughened adhesive and bonding method using the same

    US20200308358A1